Improved Functionality of Foamed WPI Solutions by Ultrasound Application - Martínez, Karina Dafne (2016)
The objective of this work was to determine the effect of ultrasound on the stability of foams of whey protein isolate. It was used an ultrasonic processor Vibra Cell Sonics, model VCX at a frequency of 20 kHz and an amplitude of 20%. For this study, two pHs and two concentrations of whey proteins were made to analyze the foaming properties by conductometric and optical methods. Measurements of the variations of surface pressure (π) with the molecular area (A) of films were also analyzed at the air-water interface with an automated KSV Langmuir type. The foam stability parameters of whey proteins were worse when ultrasound were applied at pH 7, whereas were improved or unchanged at pH 3. In other hand, bubbles images analysis showed also concentration effect through evident viscosity increase at the high concentration used.